The homebanking trends : which strategic path should Retail Banks pursue? - Pino, Ana Raquel Monteiro (2014)
One of the greatest commercial innovations developed by Retail Banks was the homebanking service. This dissertation aims at assessing the current evolution stage of the Portuguese homebanking market, as well as finding gaps vs. users’ needs/ preferences, thus projecting future trends. To do so, it was performed a national benchmark, for both the B2C and B2B segments, focused on two key pillars: image/communication, and functionalities. Further, it was conducted a survey for the both segments, to perceive what users know, use, value and would like to have in their homebankings. Based on the former analysis, the national banks were segmented in a matrix considering their performance in the two pillars studied and a clear market gap was identified. B2C users acknowledge the huge evolution the homebankings have come through in terms of functionalities; however they are not totally satisfied with their homebankings image/communication performance.